An examination of the knowledge resources used by U.P. History researchers in infromation-seeking - Apuli, Laila L.; Tarlit, Rodolfo Y. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
This study examined the knowledge resources employed by the University of the Philippines history researchers in their information related tasks at the UP Main Library Filipiniana sections. It investigated how these knowledge resources were used and helped them in information-seeking. The study aims to support the move of developing a user-centered information system and services that would closely tailor to the needs of the history researchers.
Using a qualitative, semi-structured interview schedules, six (6) history researchers and three (3) head librarians from the Filipiniana Books, Serials, and Media Services were interviewed. Materials written in foreign and local languages (other than English and Filipino) at the Filipiniana sections were also surveyed. The results of the interviews and survey were used in the analysis of the knowledge resources.
The findings of the study showed that the history researchers gather for information and build their knowledge base by consulting general reference materials, searching through the OPAC for probable materials and browsing through the library's collection. The study also confirmed the availability of a vast collection of resources written in foreign and local languages at the Filipiniana sections. These resources match the research needs and language requirements of the history researchers for such materials. The librarians also demonstrate a capacity to provide the information needs of the history researchers with regards to language and familiarity with the collection.
study, being a functional unit of a research project on the information-seeking behavior of the UP history researchers, recommends an integration of the findings of this study with the findings of the previous studies to come up with a user model that is user-centered.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman pril 2004.
Keywords: Information services -- Philippines -- Quezon City; Historians -- Philippines -- Quezon City